Staphylococcus aureus ST59: Concurrent but Separate Evolution of North American and East Asian Lineages - McClure, Jo-Ann; Lakhundi, Sahreena; Niazy, Amani; Dong, George; Obasuyi, Osahon; Gordon, Paul; Chen, Sidong; Conly, John M.; Zhang, Kunyan (Frontiers in Microbiology, 2021)
Despite initially being described in North America, Staphylococcus aureus (SA) sequence type ST59 is the most commonly isolated sequence type in Eastern Asia. The origins and evolution of this strain type remains unclear and therefore we gathered a collection of ST59 isolates from Canada and mainland China for a detailed genetic analysis of the lineage. Bayesian inference phylogenomic analysis of our isolates, along with previously published ST59 sequences indicated that the lineage could be divided into 6 distinct subgroups (WGS-1 thorough 6), each having distinct molecular characteristics. Analysis also demonstrated the concurrent but separate evolution of North American and East Asian lineages, as well as the extensive diversification of the East Asian lineage. The presence of a mobile element structure (MES) was found to be the major difference between these two continental lineages, absent in all North American isolates, and present in all East Asian ones. Other mobile genetic elements, such as the Immune Evasion Complex (IEC), Panton Valentine Leukocidin (PVL), and Staphylococcal Cassette Chromosome mec (SCCmec), showed significant variability within each sub-group and likely represents local selective pressures rather than major characteristics defining the groups. Our analysis also demonstrated the existence of a more ancient ST59 sub-lineage from North America, which was MES negative and contained some of the earliest reported ST59 isolates. Combined with the existence of a MES negative isolate from Taiwan, predicted to have appeared prior to diversification of the East Asian lineages, these results hint at the possibility of a North American origin for the lineage, which gained hold in Eastern Asia following acquisition of MES, and subsequently diversified.